Exploration of the challenges and benefits of implementing management accounting information systems in private higher education institutions: A case study at University X - Mawarti, Anggis; Yaya, Rizal (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study investigates the implementation of the Management Accounting Information System (MAIS) within Private Higher Education Institutions (PHEIs), emphasizing identifying its advantages, the challenges encountered, and strategies for optimizing its effectiveness. Design/Methodology/Approach: This research adopts a qualitative approach, utilizing in-depth interviews with key stakeholders to gather comprehensive insights. Employing a case study approach, the research focuses on University X to examine the role of MAIS in enhancing operational efficiency and supporting informed financial decision-making. The informants in this study are nine persons, including administrators and academic officials.Research findings: The findings reveal that although the MAIS has notably enhanced financial transparency and operational efficiency, several challenges remain, most notably internal limitations related to inadequate human resource capacity in system utilization and external barriers stemming from rigid regulatory frameworks.Theoretical contribution/Originality: This study offers novel critical and theoretical reasoning on exploring the challenges and benefits of implementing MAIS based on the Resource-Based View (RBV) theory and the Technology Acceptance Model (TAM).Practitioner/Policy Implication: Private Higher Education Institutions (PHEIs) should actively seek opportunities for collaboration with financial institutions and technology partners to enhance access to development financing. Furthermore, a comprehensive assessment of security measures and risk mitigation strategies is necessary for implementing MAIS, given the critical importance of data protection in digital financial environments.Research limitation: This study does not delve deeply into the technological dimensions of system security, particularly the risks associated with cyberattacks and the corresponding mitigation strategies in the context of MAIS implementation.